2004
DOI: 10.1158/0008-5472.can-04-1094
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage, Repair, and Mutation Induction by (+)- Syn and (−)- Anti -Dibenzo[ a,l ]Pyrene-11,12-Diol-13,14-Epoxides in Mouse Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…It has been shown that methylation of cytosines at CpG dinucleotides enhances the extent of acrolein binding to guanines in synthetically generated human p53 DNA fragments (17) (48). Briefly, the pSP189 plasmid was methylated in vitro using the SssI methylase (New England Biolabs) according to the manufacturer's instructions.…”
Section: Cancer Researchmentioning
confidence: 99%
“…It has been shown that methylation of cytosines at CpG dinucleotides enhances the extent of acrolein binding to guanines in synthetically generated human p53 DNA fragments (17) (48). Briefly, the pSP189 plasmid was methylated in vitro using the SssI methylase (New England Biolabs) according to the manufacturer's instructions.…”
Section: Cancer Researchmentioning
confidence: 99%
“…Dibenzo[a,l]pyrene, one of the fjord region compounds, has been demonstrated to be the most carcinogenic PAH [19]. Also benzo[c]chrysene possesses both a bay region and a fjord region in the same molecule.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Dibenzo [a,l]pyrene induced morphological cell transformation in mouse embryo fibroblast C3H10T½Cl8 cells and was more active than benzo [a]pyrene . Dibenzo [a,l]pyrene induced mutations in the cII locus of Big-Blue mouse embryonic fibroblasts (Yoon et al, 2004).…”
Section: Cyp1b1mentioning
confidence: 99%